The Relationship of Exhibition Space Design and the Success of Delivering Messages to Museum Visitors in Jakarta - Wulandari, Anak Agung Ayu; Fajarwati, Ade Ariyani Sari; Latif, Fauzia (Bina Nusantara University, 2017)
The research explored exhibition space designs, particularly the interior design elements such as circulation, lighting, and display techniques to find out whether the design elements corresponded the design principles and to find out which museum had the most ideal exhibition design that was able to deliver exhibition messages to the audience. The research applied qualitative method with case study approach in three museums in Jakarta, those were National Museums, Bank of Indonesia museum, and museum of Fine Art and Ceramic as case studies and qualitative data collecting methods through observations to get real-settings information. Data analysis and comparison of various interior elements shows that from the three case studies only Bank of Indonesia Museum has an integrated exhibition space using various interior elements; circulation and lighting design as well as display technique that support the success of a museum to deliver exhibition messages to their visitor. It can stimulate visitors senses visually, auditory, and kinetic.